'Tree and flower and leaf and grass': anachronism and J.R.R. Tolkien's botanical semiotics. (April 2015) - Forest-Hill, Lynn
Abstract: Tolkien's use of plants in his works has, over many years, been the subject of limited critical attention in spite of the diversity and complexity of that use. This paper examines a selection of Tolkien's best-known botanical references from the perspectives of various literary theories, to reveal the significance of anachronism in The Lord of the Rings. This in turn highlights the levels and forms of interpenetration by the past into the present of Middle-earth. Although the past is explicit throughout the work, attention to plants associated with specific characters and events reveals a subtext of anxiety in which the past is constructed variously as a threat, a cause or a remedy, according to the familiar, mythic, ethical or symbolic connotations of the plants depicted within the framework of Middle-earth.